Are you with me or not? Temporal synchronicity and transactivity during CSCL. (16th March 2017) - Popov, V.; van Leeuwen, A.; Buis, S.C.A.
Abstract: Do the simultaneous alignment of student activities (temporal synchronicity) and students successively building on each other's reasoning (transactivity) predict the quality of collaborative learning products? To address this question, we used a mixed‐method approach to study 74 first‐year university students who were randomly assigned to work in dyads on an ill‐defined problem of biodiversity collapse in tropical forests within a computer‐supported collaborative learning setting. The quantitative analysis revealed that neither temporal synchronicity nor transactivity was related to the quality of group products. The qualitative analysis of chat transcripts revealed that the variability between the groups could be explained by group dynamics, students' prior knowledge, confidence in managing the learning task, collaborative strategy and communication skills. The study findings could be used to optimize collaboration by informing students directly of their activities or the teachers that scaffold these activities. Lay Description: What is already known about this topic: Collaborative learning effort is influenced by how well students coordinate their activities across time and transact on each other's ideas. What this paper adds: This study examines the relation between temporal synchronicity, transactivity and the quality of group products in the context of synchronous computer‐supported collaborative learning. Neither temporal synchronicity nor transactivity was found to be directly related to the quality of group products. Implications for practice and/or policy: Collaboration groups require socio‐cognitive support not only based on the attunement of their efforts but also based on differences within groups.